2014
DOI: 10.3758/s13421-014-0439-5
|View full text |Cite
|
Sign up to set email alerts
|

Impression formation of tests: retrospective judgments of performance are higher when easier questions come first

Abstract: Four experiments are reported on the importance of retrospective judgments of performance (postdictions) on tests. Participants answered general knowledge questions and estimated how many questions they answered correctly. They gave higher postdictions when easy questions preceded difficult questions. This was true when time to answer each question was equalized and constrained, when participants were instructed not to write answers, and when questions were presented in a multiple-choice format. Results are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 10 publications
2
23
0
Order By: Relevance
“…Jones & Oberauer, 2013); they may occur because initial information receives more rehearsal (Tan & Ward, 2008), more attention at encoding (Farrell & Lewandowsky, 2002;Page & Norris, 1998), or because initial information is more distinct in the absence of proactively interfering information (Brown et al, 2007;Henson, 1998). Importantly, primacy effects have also been reported in impression formation (Anderson & Hubert, 1963;Asch, 1946;Belmore, 1987;Dreben, Fiske, & Hastie, 1979;Jackson & Greene, 2014; also see Hogarth & Einhorn, 1992;van Overwalle & Labiouse, 2004) and long-term memory (Copeland, Radvansky, & Goodwin, 2009;Li, 2010;Nairne, 1991;Neath, 2010;Rubin, 1977). For example, when judging a person after receiving a series of descriptors, initial items have a stronger influence on the retrospective judgment than later ones (e.g., Dreben et al, 1979); when recalling a novel, the first chapters of the novel show a recall advantage (Copeland et al, 2009).…”
Section: Introductionmentioning
confidence: 90%
“…Jones & Oberauer, 2013); they may occur because initial information receives more rehearsal (Tan & Ward, 2008), more attention at encoding (Farrell & Lewandowsky, 2002;Page & Norris, 1998), or because initial information is more distinct in the absence of proactively interfering information (Brown et al, 2007;Henson, 1998). Importantly, primacy effects have also been reported in impression formation (Anderson & Hubert, 1963;Asch, 1946;Belmore, 1987;Dreben, Fiske, & Hastie, 1979;Jackson & Greene, 2014; also see Hogarth & Einhorn, 1992;van Overwalle & Labiouse, 2004) and long-term memory (Copeland, Radvansky, & Goodwin, 2009;Li, 2010;Nairne, 1991;Neath, 2010;Rubin, 1977). For example, when judging a person after receiving a series of descriptors, initial items have a stronger influence on the retrospective judgment than later ones (e.g., Dreben et al, 1979); when recalling a novel, the first chapters of the novel show a recall advantage (Copeland et al, 2009).…”
Section: Introductionmentioning
confidence: 90%
“…1 Research in social and cognitive psychology has found a disproportionate influence of early hypotheses on final judgments. [2][3][4][5][6] This has been attributed to the working memory being less loaded at the start of a judgment task; therefore, initial information receives more attention and is better encoded. 3 Early impressions can be maintained and carried through to the final judgment via biased information search 7 and/or biased information processing.…”
mentioning
confidence: 99%
“…Previous research has demonstrated that starting a test with easy questions leads to more optimistic evaluations of performance after the test (Jackson & Greene, 2014;Weinstein & Roediger, 2010, 2012. The current studies were conducted to determine whether exposure to general knowledge questions in a particular difficulty order would diminish the question order bias in evaluations of test performance.…”
Section: Discussionmentioning
confidence: 97%